BIOTECHNOLOGICAL APPROACHES TO VEGETABLE CROP BREEDING - V.F. Pivovarov; N.A. Shmykova; T.P. Suprunova (Овощи России, 2011)
The biotechnological methods of plant cell culture in vitro are represented in the article. Recent developments in the field of clonal micropropagation, androgenesis, gynogenesis, and genetic transformation of vegetable crops are shown. Importance of utilization of biotechnological approaches for successful development of agriculture is underlined.